Acetabular Anteversion Changes Due to Spinal Deformity Correction: Bridging the Gap Between Hip and Spine Surgeons - Buckland, Aaron J; Vigdorchik, Jonathan; Schwab, Frank J; Errico, Thomas J; Lafage, Renaud; Ames, Christopher; Bess, Shay; Smith, Justin; Mundis, Gregory M; Lafage, Virginie (Journal of bone and joint surgery. American volume, 2015)
Hip osteoarthritis often coexists with adult spinal deformity, an abnormality in which sagittal spinopelvic malalignment is present. Debate exists whether to perform spinal realignment correction or total hip arthroplasty first. Hip extension and pelvic tilt are important compensatory mechanisms in the setting of sagittal spinopelvic malalignment and change after spinal realignment. We performed this study to evaluate the effect that the spinal realignment surgical procedure has on acetabular anteversion. This study is a retrospective review of a multicenter, prospective, consecutive database of patients with adult spinal deformity who underwent surgical spinal realignment. Only patients who already had undergone a total hip arthroplasty prior to the spinal realignment procedure were retained for analysis. Patients were excluded if they had insufficient imaging or large-head, metal-on-metal bearings or they had undergone revision total hip arthroplasty in the study period. Acetabular anteversion was calculated via the ellipse method on a standing, posterior-anterior, 90-cm radiograph with a well-centered pelvis. Anteversion was measured preoperatively and at six weeks or three months after the spinal realignment procedure. Spinopelvic parameters measured included pelvic incidence, pelvic tilt, sacral slope, lumbar lordosis, T1 pelvic angle, sagittal vertical axis, T1-spinopelvic inclination, and thoracic kyphosis. Forty-one hips (thirty-three patients) were identified. Acetabular anteversion significantly reduced (p < 0.001) after spinal correction by mean change of -4.96° (range, -22.32° to +2.36°). The change in anteversion correlated with the changes in sagittal pelvic orientation (0.828 for the pelvic tilt, -0.757 for the sacral slope, and -0.691 for the lumbar lordosis) and global spinopelvic alignment (0.579 for the sagittal vertical axis and 0.585 for the T1 pelvic angle). Regression analysis revealed that anteversion decreased by 1° for each of the following spinopelvic parameter changes (p < 0.001): 1.105° for spinopelvic tilt, 1.032° for sacral slope, and 3.163° for lumbar lordosis. Patients with spinopelvic malalignment had a high prevalence of excessively anteverted acetabular components. Sagittal spinal correction following total hip arthroplasty resulted in reduced acetabular anteversion, which may have implications for stability. Changes in anteversion are most closely related to changes in pelvic tilt in an almost one-to-one ratio.